Associations Between Domain Differentiated Sibling Conflict and Adolescent Problem Behavior. Issue 3 (30th January 2020) - Odudu, Christopher; Williams, Maya; Campione‐Barr, Nicole
Abstract: Objective: The present study examines sibling conflict across two domains and their associations with externalizing behaviors (discussed as problem behavior in this article) 1 year later. Background: The close‐natured relationship of siblings often leads to sibling conflict. Previous research has found that sibling conflict can be categorized into the following two content domains: invasion of personal (IP) and equality and fairness (EF). These domains of conflict are differential predictors of adolescent adjustment problems, particularly internalizing problems; however, less is known about the link between specific domains of conflict and problem behavior. Method: Using Actor Partner Interdependence Modeling, purposive sampling was conducted to recruit a sample of 145 sibling dyads ( N = 290) adolescents in 8th, 10th, or 12th grades with a sibling no more than 4 years younger. Adolescents were administered questionnaires assessing the frequency and intensity of sibling conflict and individual problem behavior. Results: The results suggest that more intense IP and EF sibling conflicts were more strongly associated with later adjustment problems than frequent IP and EF sibling conflicts. Furthermore, mixed‐sex sibling dyads and younger siblings were at greater risk for later problem behavior when engaged in intense IP and EF sibling conflicts. Conclusion: The findings of the present study underscore the importance of considering the content of sibling conflict and the contextual factors of siblings as they have differential impacts on adolescent problem behavior.